2016
DOI: 10.1002/jmri.25430
|View full text |Cite
|
Sign up to set email alerts
|

Fat‐suppressed T2 mapping of femoral cartilage in the porcine knee joint: A comparison with conventional T2 mapping

Abstract: 2 J. Magn. Reson. Imaging 2017;45:1076-1081.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Previous studies [ 15 , 16 ] suggested that compared with that on conventional T2 mapping, the T2 value is reduced on in F2 T2 mapping of the knee articular cartilage. Rye et al [ 16 ] demonstrated significantly lower T2 values on FS T2 mapping than on conventional T2 mapping with porcine knees.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies [ 15 , 16 ] suggested that compared with that on conventional T2 mapping, the T2 value is reduced on in F2 T2 mapping of the knee articular cartilage. Rye et al [ 16 ] demonstrated significantly lower T2 values on FS T2 mapping than on conventional T2 mapping with porcine knees.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [ 15 , 16 ] suggested that compared with that on conventional T2 mapping, the T2 value is reduced on in F2 T2 mapping of the knee articular cartilage. Rye et al [ 16 ] demonstrated significantly lower T2 values on FS T2 mapping than on conventional T2 mapping with porcine knees. Paakkari et al [ 15 ], similar to previous ex vivo results, demonstrated lower T2 values on FS T2 mapping than on conventional T2 mapping in healthy human volunteers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The T2 value of Osag T2MAP is associated with free water content in cartilage tissue. The more severe the cartilage damage, the more free water and the higher the T2 value; thus, the T2 value is an objective and reliable marker [37]. The results of Osag T2MAP and their underlying causes were similar to those of OSag-fs PD.…”
Section: Discussionmentioning
confidence: 57%
“…Using anterior-to-posterior frequency-encoding directions, the chemical shift artifact seemed to be more apparent in tibial cartilage than talar cartilage in our study. The degree of chemical shift for the segmentation, as well as calculated T1rho and T2 values, can vary depending on the cartilage orientation with respect to the magnetic field (49).…”
Section: Discussionmentioning
confidence: 99%